Synergistic Interaction of Sweet potato chlorotic stunt virus (Crinivirus) with Carla-, Cucumo-, Ipomo-, and Potyviruses Infecting Sweet Potato - Untiveros, M.; Fuentes, S.; Salazar, L.F. (Scientific Societies, 2007)
Co-infection of Sweet potato chlorotic stunt virus (SPCSV, genus Crinivirus) with Sweet potato feathery mottle virus (SPFMV, genus Potyvirus) results in sweet potato virus disease (SPVD), a synergistic disease that is widely distributed in the sweet potato (Ipomoea batatas) growing regions of the world. Since both SPCSV and SPFMV are common and often detected as part of multiple co-infections of severely diseased plants, the occurrence of synergistic interactions with other viruses was investigated. Data from this study show that SPCSV, but not SPFMV, can cause synergistic diseases in sweet potato with all viruses tested, including members of the genus Potyvirus (Sweet potato latent virus, Sweet potato mild speckling virus), Ipomovirus (Sweet potato mild mottle virus), Cucumovirus (Cucumber mosaic virus), and putative members of the genus Carlavirus (Sweet potato chlorotic fleck virus and C-6 virus). The synergism was expressed as an increase in the severity of symptoms, virus accumulation, viral movement in plants, and as an effect on yield of storage roots. The presence of a third different virus in plants affected with SPVD increased the severity of symptoms even further compared with SPVD alone. There was a positive correlation between increase in virus accumulation and symptom expression in double and triple SPCSV-associated co-infections. The epidemiological implications of the results are discussed.